PREFERENSI PEREMPUAN TERHADAP PASAR TRADISIONAL DAN SWALAYAN DALAM PERILAKU BELANJA MASYARAKAT DESA DI KECAMATAN JATINOM KABUPATEN KLATEN - , HERU ARIFIYANTO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In the provision of shopping centers in the implied contained many issues related to the strategically population / consumers served. The aim of this research is to know the real condition of social economy in rural communities knowing the public spending and vibrant things actually influence it, and know what it is to be preferred villagers in choosing traditional markets and supermarkets as a shopping. Research survey, using methods by taking sample research in jatinom sub-district. Data collected by descriptive analysis using the frequency to know the level of community participation, and factors affecting the different levels of preference against markets and supermarkets in behavior public spending viilage. The results of these studies are real differences in social conditions economic villagers with regard to the number of members of the family, educational level, a livelihood, ownership of motor vehicles, and the mobility of villagers. The social economy, access, and social interaction villagers affected manners s villagers. Preference villagers to traditional markets and supermarkets based on personal preference and preference geographical location. The pattern of the expenditure in accordance with the local villagers or the budget expenditures for the local villagers.